Evaluation of Social Protection Policies for Vulnerable Groups: A Study on the Implementation of Social Safety Net Programs in Urban and Rural Areas - Trisnawati Trisnawati; Rashid Rahman; Benjamin Carter (Journal of Social Science Utilizing Technology, 2025)
Background. This study evaluates the implementation of the Jaring Pengaman Sosial (JPS) program, focusing on vulnerable groups in urban and rural areas in Indonesia. Social protection policies are critical in addressing the needs of marginalized populations, especially during times of economic instability. However, the effectiveness and accessibility of such programs often vary significantly between urban and rural regions due to differences in infrastructure, administrative capacity, and socio-economic conditions. Purpose. The primary aim of this research is to assess the impact of JPS on urban and rural beneficiaries, examining differences in access to benefits, program satisfaction, and the specific challenges faced by each group. Method. A mixed-methods approach was used, combining quantitative surveys and qualitative interviews with 500 participants (250 urban and 250 rural). Data analysis revealed that urban beneficiaries had higher satisfaction rates and better access to benefits, particularly cash transfers, while rural beneficiaries faced logistical barriers, including delays in benefit distribution and limited access to information. Results. The findings highlight significant disparities in the implementation and effectiveness of social protection programs across geographic regions. Conclusion. The study concludes that tailored interventions are necessary to ensure equitable access to benefits, particularly in rural areas, and recommends improving program delivery and targeting mechanisms to better address regional needs.